Indigenous home remedies as applied in Shirpur Taluka of Dhule district (Maharashtra) India - Patil2, D. R. Patil1, P. S. Patil1; D. A. (Current Botany, 2011)
The authors investigated Shirpur taluka of Dhule District (Maharashtra) for indigenous home remedies used to combat various human afflictions. Botanicals used in cuisine and commonly grown in homestead gardens are documented for their utilities especially against common afflictions. This paper includes information on 21 species belonging to 21 genera and 15 families of angiosperms. The medicinal recipes are in the form of decoction, infusion, extract, juice, oil, powder, paste and ash. Domestic substances are also added while preparing recipes. Raw parts or cooked ones are also employed in few cases. They are administered to benefit in about 17 different human afflictions. The medicines consist usually of sole drug, except few. Botanicals commonly used as spices, edibles and locally religious or ornamental ones also find place in the local remedies. Majority of them are under cultivation, while few others are purchased from markets. This paper highlights secondary applications of these botanicals, although they are employed principally for other purposes. The veracity of these indigenous drugs is desirable for further scientific examination.